THE CORRELATION BETWEEN LEARNING INDEPENDENCE, NUMERICAL ABILITY, AND LEARNING MOTIVATION IN MATHEMATICS LEARNING OUTCOMES - Muhammad Sugiarto; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Low student Mathematics learning Outcomes are associated with many factors. Learning independence, numerical ability, and motivation to learn are three factors that are suspected of correlating with mathematics learning outcomes Student. This study is purposed to determine whether or not a positive and significant correlation between Learning Independency, Numerical Ability, and learning Motivation in Mathematics Learning Outcomes Student in Grade VIII Junior High School (SMP) Muhammadiyah 1 Godean Sleman even Semester Academic Year of 2017/2018. This research population was all students grade VIII SMP Muhammadiyah 1 Godean Sleman in odd Semester academic year 2017/2018 consisting of 5 classes with 169 students. Sampling class using a random sampling technique to class, which obtained class VIII B as sample class and class VIII E as a trial class. This research using a random sampling technique. Data collection techniques were conducted by questionnaire and test methods. The data collection instrument uses a learning independence questionnaire, numerical ability test, learning motivation questionnaire, and learning outcomes test. The instrument test uses a validation test, a discrimination test, and a reliability test. The prerequisite analysis test uses the normality test, independence test, and linearity test. Data analysis for hypothesis testing using simple linear regression analysis and multiple regression and correlation analysis. The result showed a positive and significant correlation between learning independence, numerical ability, and learning motivation in mathematics learning outcomes with , double correlation coefficient (R) 0,637, and double determination coefficient equal to 0,406. While the double regression equation , the relative contribution , the relative contribution , the relative contribution , and effective contribution , effective contribution , and effective contribution